Analisis risiko pembiayaan murabahah dalam sistem perbankan syariah : studi literatur - Anggrainie, Agustina (Maliki Interdisciplinary Journal, 2025)
Murabahah-based financing is one of the main services in the Islamic banking industry. This transaction is carried out through a buying and selling mechanism in which the price includes a profit margin agreed upon by both parties. Although it does not involve interest elements, Murabahah still carries significant risks—financial, operational, and compliance-related with Sharia principles. This article aims to identify the various types of risks associated with Murabahah financing and propose appropriate mitigation strategies to ensure the sustainability of the Islamic financial system. Islamic banks must strengthen their customer selection process with a 5C analysis, conduct regular monitoring and evaluation of disbursed financing, and utilize collateral and Islamic insurance as additional protection. Internal oversight, regular audits, and customer education are also crucial to ensure compliance with Islamic principles and minimize the potential for non-performing loans.